Investigation of the deformation behavior of aluminum micropillars produced by focused ion beam machining using Ga and Xe ions. (15th January 2017) - Xiao, Y.; Wehrs, J.; Ma, H.; Al-Samman, T.; Korte-Kerzel, S.; Göken, M.; Michler, J.; Spolenak, R.; Wheeler, J.M.
Abstract: Sample geometries for micro-mechanical testing, e.g. micro-pillars and micro-cantilevers are primarily produced using gallium focused ion beam technology. However, the effects of the gallium ions on the mechanical properties of metals which are embrittled by liquid metal gallium are still unknown. In this work, micro-compression samples from single crystalline and ultrafine-grained aluminum are fabricated using both xenon and/or gallium ions. The different ions have little effect on the yield strength of single crystalline aluminum. However, for the ultrafine-grained aluminum, the strength is reduced with increasing Ga dose, and considerable differences in the deformation morphology and resulting microstructures are observed.